Ips and woodborer insects in Pinus montezumae trees damaged by forest fires - Fonseca-González, Juana; De Los Santos-Posadas, Héctor Manuel; Llanderal-Cázares, Celina; Cibrián-Tovar, David; Rodríguez-Trejo, Dante Arturo; Vargas-Hernández, Jesús (Instituto de Ecología, A.C., 2016)
The proportion of Ips galleries with respect to other bark beetles (Pityophthorus, Hylastes, Hylur gops) and larvae of Cerambycidae was analyzed through logistic regression in its interaction with tree diameter and three variables of damage by fire (crown scorch classes, bole char height and live crown length). Ips gallery proportion diminishes as tree diameter and bole char height increase, whereas that proportion grows with the increment in live crown length. In trees with totally scorched crown, but with live terminal buds, the proportion of galleries of woodborer insects increases and the same happens at increasing bole char height in trees with diameter superior to 30 cm.